(3TQM CTcGd GdJCSjSs - (3ehSi Hf eMeO Hf eMehO GdQhej, UdGM GdOjf GdeYQha HbGVj RGOg ehSi LdHj , J fMh (B840 (3g` s; (3TeS GdOjf eMeO Hf GTQa GdSeQbfOj,J (B600 (3g` ? s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF HbOQ , hbOQ dg eGjdjb Hg ef CTcGd hUhQ Ke Cf GdeNJUQ GdeSei HCTcGd GdJCSjS ddEeGe s
(3BNQgG (B:s
(3hgPg GdCTcGd GdNeSI GdCNjQI ef KGfjI cJGH GdCUhd dChbdjOS s
(3CTcGd GdJCSjS (B: (3dTeS GdOjf eMeO Hf CTQa GdSeQbfOi GdeJhai SfI (B600s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B212 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B55 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs